A novel methane detection system based on InGaAsP distributed feedback laser - Cong, Menglong; Guo, Shuxu; Wang, Yiding (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The authors report a novel methane detection system based on InGaAsP DFB (distributed feedback) laser using the WMS-2f (wavelength modulation spectroscopy) to prompt the sensitiv-ities of TDLAS (tunable diode laser absorption spectroscopy) measurement technology at the R(3) transition of the 2ν3 band of methane. The system employs a novel signal processing to cancel emitter-amplitude variations as well as changes in the optical transmission not due to the target gas. High accuracy and low detecting limit (about 1 ppm) are achieved at normal air pressure and room temperature. Excellent stability and fast response are also found based on the detection system in 30 days. These results suggest that our system is a good candidate for CH4 detectors.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 639-648
Keywords: optyka; optical sensor; methane; distributed feedback (DFB) laser